Pengaruh Komunikasi Kepemimpinan Terhadap Loyalitas Karyawan pada PT Global Technology Resources (Hargadunia.Com) - Fatimah; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Leadership communication is the most important factor in persuading people to maintain their organization loyalty. This study aims to determine the relationship between leadership communication and employee loyalty at PT Global Technology Resources (HargaDunia.Com). This study use the positivist paradigm, a quantitative methodology, and the survey method to collect data from 50 respondents via questionnaires completed by all employees using techniques of saturated sampling. This study applies the S-R theory, with leadership communication as the stimulus and employee loyalty as the reaction. This study's hypothesis was evaluated using validity, reliability, descriptive analysis, correlation coefficient, simple linear regression, and T tests. The correlation coefficient test or the degree of link strength "r" returned a value of 0.598, demonstrating that leadership communication (X) and employee loyalty are related (Y). Since 0.00 > 0.05, H1 is accepted and H0 is denied, showing that variable (X) has a significant effect on variable (Y) (Y).